Travel, transport and communication to and from Ireland, c. AD 400-1100: an archaeological perspective - Loveluck, Chistopher; O'Sullivan, Aidan (Palgrave MacMillan, 2016)
In this paper we examine the extensive new archaeological evidence for the early Irish medieval economy, trade and exchange, evidence which has accrued during the explosion of developer-led archaeological research in Ireland in recent decades and has highlighted the importance of the Atlantic-facing regions of Europe in helping to drive the social, economic, and political transformations of early medieval western Christendom. An archaeological re-assessment of links between Ireland, Britain and continental Europe is, therefore, an essential prerequisite to understanding the role and impact of the Irish in early medieval Europe. An assessment of this role between the fifth and eleventh centuries has to be conducted within the context of the maritime cultural landscapes of Atlantic Europe and the Channel, and the principal river ‘transport corridors’ leading into the interior of continental Europe and ultimately to the Mediterranean.